A pancreatic zone at higher risk of fistula after enucleation - Pauline Duconseil; Ugo Marchese; Jacques Ewald; Marc Giovannini; Djamel Mokart; Jean-Robert Delpero; Olivier Turrini (World Journal of Surgical Oncology, 2018)
Abstract Background To determine predictive factors of postoperative pancreatic fistula (POPF) in patients undergoing enucleation (EN). Methods From 2005 to 2017, 47 patients underwent EN and had magnetic resonance imaging available for precise analysis of tumor location. Three pancreatic zones were delimited by the right side of the portal vein and the main pancreatic head duct (zone #3 comprising the lower head parenchyma and the uncinate process). Results The mortality and morbidity rates were 0% and 62%, respectively. POPF occurred in 23 patients (49%) and was graded as B or C (severe) in 15 patients (32%). Four patients (8.5%) developed a postoperative hemorrhage, and 5 patients (11%) needed a reintervention. In univariate and multivariate analyses, the pancreatic zone was the unique predictive factor of overall (P = .048) or severe POPF (P = .05). We did not observe any difference in postoperative courses when comparing the EN achieved in zones #1 and #2. We noted a longer operative duration (P = .016), higher overall (P = .017) and severe POPF (P = .01) rates, and longer hospital stays (P = .04) when comparing the EN achieved in zone #3 versus that in zones #1 and #2. Patients who underwent EN in zone #3 had a relative risk of developing a severe POPF of 3.22 compared with patients who underwent EN in the two other pancreatic zones. Conclusion Our study identifies the lower head parenchyma and the uncinate process as a high-risk zone of severe POPF after EN. Patients with planned EN in this zone could be selected and benefit from preoperative and/or intraoperative techniques to reduce the severe POPF rate.